Time and voltage dependence of anodic zinc oxide nanoparticle structure using oxalic acid electrolyte - Semblante, Oliver D. (Animo Repository, 2024)
At 20 volts (V) applied potential, granular ZnO particles with particle sizes ranging from sub-micron to tens of microns and nano-sized ZnO networks having dimensions of 30-70 nm were observed after 30 minutes and 10 seconds of anodization of zinc in 0.3 M oxalic acid electrolyte, respectively. Sustaining the 10-second reaction time, anodization of zinc in 0.3 M. oxalic acid electrolyte formed densely distributed rod-like structures with particle size about 80-150 nm, rod-like structures with some networks starting to form, and network structure of sizes 30-70 nm of zinc oxide at 10 V, 15 V, and 20 V applied potential, respectively.